2008
DOI: 10.1038/clpt.2008.150
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin With Fluoroquinolones, Sulfonamides, or Azole Antifungals: Interactions and the Risk of Hospitalization for Gastrointestinal Bleeding

Abstract: Objective-To determine whether a potential pharmacokinetic interaction between warfarin and orally administered anti-infectives increases the risk of hospitalization for gastrointestinal (GI) bleeding in warfarin users.Methods-We conducted a nested case-control and case-crossover study in US Medicaid data. Logistic regression was used to determine the association between GI bleeding and prior use of ciprofloxacin, levofloxacin, gatifloxacin, cotrimoxazole, or fluconazole, all versus no exposure and versus ceph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
101
0
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(111 citation statements)
references
References 30 publications
2
101
0
8
Order By: Relevance
“…101,104 There was less consistency in the relationship between COX-2-selective NSAIDs plus VKAs vs VKA alone and bleeding outcomes, varying from a nonsignifi cant RR of 1.4 (95% CI, 0.44-4.30) to a signifi cant OR of 3.1 (95% CI, 1.4-6.7). 100 105,112,113,115 There is a suggestion that cephalosporins (ignoring the anomalously high RR provided for cefradine), metronidazole, amoxicillin, amoxicillin/clavulanic acid, doxycycline, and fl uconazole may have some impact on bleeding risk, but these drugs in general are insuffi ciently studied. [112][113][114] Similarly, some studies suggest that selective serotonin reuptake inhibitors, tramadol, acetaminophen, coenzyme Q, and ginger may increase the risk of bleeding, but these also require confi rmation.…”
Section: Vka Drug Interactions To Avoidmentioning
confidence: 99%
See 1 more Smart Citation
“…101,104 There was less consistency in the relationship between COX-2-selective NSAIDs plus VKAs vs VKA alone and bleeding outcomes, varying from a nonsignifi cant RR of 1.4 (95% CI, 0.44-4.30) to a signifi cant OR of 3.1 (95% CI, 1.4-6.7). 100 105,112,113,115 There is a suggestion that cephalosporins (ignoring the anomalously high RR provided for cefradine), metronidazole, amoxicillin, amoxicillin/clavulanic acid, doxycycline, and fl uconazole may have some impact on bleeding risk, but these drugs in general are insuffi ciently studied. [112][113][114] Similarly, some studies suggest that selective serotonin reuptake inhibitors, tramadol, acetaminophen, coenzyme Q, and ginger may increase the risk of bleeding, but these also require confi rmation.…”
Section: Vka Drug Interactions To Avoidmentioning
confidence: 99%
“…100 105,112,113,115 There is a suggestion that cephalosporins (ignoring the anomalously high RR provided for cefradine), metronidazole, amoxicillin, amoxicillin/clavulanic acid, doxycycline, and fl uconazole may have some impact on bleeding risk, but these drugs in general are insuffi ciently studied. [112][113][114] Similarly, some studies suggest that selective serotonin reuptake inhibitors, tramadol, acetaminophen, coenzyme Q, and ginger may increase the risk of bleeding, but these also require confi rmation. 103,105,106,116,117 Recommendations 3.8.…”
Section: Vka Drug Interactions To Avoidmentioning
confidence: 99%
“…60 Two recent population-based studies have shown that among patients receiving warfarin, the use of trimethoprim-sulfamethoxazole is associated with a two-to threefold increased risk of gastrointestinal hemorrhage relative to other antibiotics. 61,62 Interactions involving drug transporters Trimethoprim also inhibits the renal organic cation transporter and sulfamethoxazole inhibits the organic anion transporter, 68,69 transport systems that normally facilitate the renal elimination of several drugs. In children receiving methotrexate, treatment with trimethoprim-sulfamethoxazole decreases organic anion transporter-mediated renal clearance of methotrexate by 40%, 23,24 increasing the risk of methotrexate toxicity (including cytopenia, mucositis, hepatotoxicity and gastrointestinal symptoms).…”
Section: Interactions Involving the Cytochrome P450 Enzyme Systemmentioning
confidence: 99%
“…Amoxicillin/clavulanic acid (amoxiclav), a member of the penicillin class, also has been suggested to potentiate the effects of warfarin [3]. Several case reports and retrospective studies stated that amoxiclav increased INR and/or the risk of bleeding with an odds ratio (OR) of 7 in patients treated with warfarin [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%